Covid-19 Pandemic And Torism SMES: Exploring Impact, Strategies, Required Policies, And Business Sustainability - Syekh Idrus; Rico Nur Ilham (International Journal of Artificial Intelligence Research, 2022)
This paper examines the impacts, strategies, policies needed, and the sustainability of small and medium enterprises in the tourism sector (SME-Tourism) in the face of the Covid-19 pandemic. We used an exploratory research design with a survey approach to 384 SME-Tourism in Indonesia in 2022. The data was collected through interviews with the help of a questionnaire. The data analysis used a simple descriptive analysis model, and the results showed that the pandemic had a broad impact on SME-Tourism, and the impacts tended to overlap with each other. This shows the complexity of their problem. To that end, they implemented a number of strategies to reduce the worse impact. Unfortunately, the strategy they use is not effective if it is not supported by a number of policy packages from the government. Without policy support, most of them cannot predict the viability of their business. Only a small percentage are optimistic that it will last for the next three months, while others are pessimistic that it will last less than three months. Therefore, the right policy package is highly expected from the government, while SME-Tourism itself needs to increase creativity and innovation in various aspects of its business, including in the fields of marketing, production, finance, human resources, and organization